Entrepreneurship development in Malaysia: Based on the findings of the Global Entrepreneurship Monitor (GEM) 2009 - Mohd Nor, Leilanie; Yusof, Mohar; Amat Sapuan, Dewi; Xavier, Siri Roland (ASEAN Universities Consortium of Enterpreneurship Education (AUCEE), 2010)
This paper presents the results and findings of the Global Entrepreneurship Monitor (GEM) 2009 for Malaysia in which the country is represented by the research team from the Bank Rakyat School of Business and Entrepreneurship (BRSBE), Universiti Tun Abdul Razak (UniRazak). Notably, GEM has become the world's most comprehensive research consortium dedicated to understanding the relationship befween entrepreneurship and national economic development. It has provided the most comprehensive comparative data about attitudes toward entrepreneurs, start-up business activities, and plans for starting and building businesses, globally, by country, by geographic region and by phase of economic development. The 2009 study, the 11th in the GEM series, was based on interviews with at least 2,000 individuals in each participating country. This paper focuses and highlights the results and findings on Malaysia and in some related aspects, will compare Malaysia's standings against other participating countries in the study especially with the other 4 countries from the Asia Pacifc region namely China, Hong Kong, Japan and Republic of Korea (54 countries participated in the GEM 2009 study). This paper presents and discusses on the results and findings on the characteristics of entrepreneurial activiry, entrepreneurial attitudes and entrepreneurial perceptions which have been collected via the Adult Population Survey (APS). Several recommendations are drawn from the discussion.